Efficient 2D NZCC/MD code for SAC-OCDMA systems based on direct spectral/spatial dimension detection and WF - Redouane Berber; Mohammed Chetioui; Fatima Bouasria; Abdelhakim Boudkhil; Mehdi Damou; Fatima Zohra Driss Khoudja (Universitas Ahmad Dahlan, 2023)
One dimensional (1D) spectral amplitude coding-optical code division multiple access (SAC-OCDMA) systems are generally known by a strict limitation in the ‎number of users that can simultaneously connect. A main solution to overcome this drawback consists of ‎constructing a two-dimensional (2D) structure using a new hybrid spectral/spatial code through combining a ‎‎one dimensional new zero cross correlation code (NZCC) to a one dimensional multi-diagonal code (1D MD) to easily provide null cross-correlation properties and totally remove the ‎multiple access interferences. Accordingly, this research paper describes an easy and fast technique to ‎construct a hybrid two-dimensional NZCC-MD code based on a non diagonal matrix for SAC-OCDMA systems with‎ direct spectral/spatial dimension (SDD) detection technique and water-filling (WF) optimization. ‎The novel code presents many advantages such as less complex structure, acceptable code length as well as ‎the possibility to construct it for any weight value. The proposed code demonstrates a very good ‎performance for systems with high debit and high simultaneous user number keeps a less complex structure.